2012
DOI: 10.1179/1465312512z.00000000038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical acceptability of two self-etch adhesive resins for the bonding of orthodontic brackets to enamel

Abstract: The shear bond strengths of the self-etch adhesive resin cements may be inadequate to successfully bond orthodontic brackets to enamel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Furthermore, variances in the mode of fracture between universal self-etch and total-etch adhesives are in accordance with the study of Schnebel et al . [ 29 ], which revealed that failure occurs mostly at the bracket–adhesive interface for total-etch adhesives, leaving the enamel surface intact, but more chair time is needed to eliminate the residual adhesive. Self-etched universal adhesives resulted in more failures at the enamel–adhesive interface.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, variances in the mode of fracture between universal self-etch and total-etch adhesives are in accordance with the study of Schnebel et al . [ 29 ], which revealed that failure occurs mostly at the bracket–adhesive interface for total-etch adhesives, leaving the enamel surface intact, but more chair time is needed to eliminate the residual adhesive. Self-etched universal adhesives resulted in more failures at the enamel–adhesive interface.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some currently available adhesive systems can dissolve the smear layer, the most common technique used for orthodontic brackets to enamel is still the total etch adhesive using orthophosphoric acid [5,6]. This adhesive system generates a rough area on the surface and microporosities for micromechanical retention which allows the incorporation of small resin "tags" within the enamel surface, thereby creating microscopic mechanical interlocks between the enamel and resin [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Enamel fractures were frequently observed on tooth surfaces with brackets bonded through etch and rinse technique. Various factors can influence the bonding strength force of the brackets to the enamel such as the type of adhesive, the thickness of the adhesive layer, humidity, geometry of the bracket base,oral habits,etc, but the main one seems to be the etching technique [5][6][7][8][9].…”
Section: Resultsmentioning
confidence: 99%
“…Schnebel states that the adhesive force of the selfetching systems is not appropriate for bracket bonding and suggests that in order to gain enough bond strength orthodontists should use the classic etching technique [7]. The type of adhesive influences the bond strength, the risc of damaging the enamel and the presence of composite resin on the tooth surface [8].…”
Section: Introductionmentioning
confidence: 99%